Directed Dehydrogenative Copper‐Catalyzed C−H Thiolation in Pseudo‐Anomeric Position of Glycals using Thiol and Thiosugar Partners. Issue 18 (6th September 2022) - Li, Linlin; Mahri, Lynda; de Robichon, Morgane; Fatthalla, Maha; Ferry, Angélique; Messaoudi, Samir
Abstract: The synthesis of 1‐thiotrehaloses and thioglycals by a directed copper‐catalyzed dehydrogenative C−H thiolation of the pseudo‐anomeric bond of glycals is described. The use of aminoquinoline‐containing glycals as well as thiosugars or thiols as coupling partners led to the synthesis of a library of thioglycosides in moderate to good yields. Abstract :